2004
DOI: 10.1159/000079865
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Cyclooxygenase-2 Inhibition on Renal Function in Heterozygous Ren-2-Transgenic Rats on Normal or Low Sodium Intake

Abstract: Background/Aims: Since there are no data available so far on the role of renal cyclooxygenase-2 (COX-2) in hypertensive Ren-2-transgenic rats (TGR), in the present study we evaluated renal cortical COX-2 protein expression and prostaglandin E2 (PGE2) concentrations as well as renal functional responses to acute COX-2 inhibition in male heterozygous TGR and in normotensive Hannover Sprague-Dawley (HanSD) rats fed either a normal-sodium (NS) or a low-sodium (LS) diet. Methods: In rats fed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Furthermore, we found that severe sodium depletion substantially attenuated BP in TGR at all ages, but did not alter plasma or kidney ANG II levels in TGR. These findings are in good agreement with our recent observation that long-term treatment with LS diet immediately after the weaning period (starting at 28 days of age) markedly reduced BP in heterozygous TGR almost to normotensive levels [37,38].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, we found that severe sodium depletion substantially attenuated BP in TGR at all ages, but did not alter plasma or kidney ANG II levels in TGR. These findings are in good agreement with our recent observation that long-term treatment with LS diet immediately after the weaning period (starting at 28 days of age) markedly reduced BP in heterozygous TGR almost to normotensive levels [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, previous studies have proved that the activity of the RAS is inversely related to the level of salt intake, and that the increased activity of RAS during sodium restriction is a compensatory mechanism capable of maintaining normal sodium balance, stable extracellular fluid volume and BP across a wide range of sodium retention [22,[57][58][59][60]. It has been shown that heterozygous TGR respond to increased dietary salt intake by exacerbation of their hypertension [35,36] and that sodium restriction resulted in marked attenuation of the development of hypertension in heterozygous male TGR [37,38]. These findings indicate that TGR carry an important salt-sensitive component of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our method was previously validated in this laboratory by Heller and Hellerova [unpublished observation], who demonstrated a very good correlation between indirect tail-cuff measurements and direct measurements of BP simultaneously obtained through an arterial catheter. Since the time of this validation we have employed the tail-cuff method routinely in our laboratory [28,29,35,36] .…”
Section: Series 1: Assessment Of Systolic Bp Plasma and Kidney Ang Imentioning
confidence: 99%
“…Since an emerging body of evidence indicates that TGR exhibit a salt-sensitive component of hypertension [27][28][29][30] , and since we have recently demonstrated that this salt sensitivity in male heterozygous TGR is associated with a loss of the normal regulatory effect of changes in dietary salt intake on ANG II production [17] , the second aim of the present study was to delineate the effects of oral salt loading and salt depletion on BP and plasma and kidney ANG II levels in female heterozygous TGR and age-matched female HanSD rats and to compare these responses to changes in sodium balance with those in male TGR and HanSD rats.…”
Section: Introductionmentioning
confidence: 99%